Association of arginine vasopressin with low atrial natriuretic peptide levels, left ventricular remodelling, and outcomes in adults with and without heart failure. (3rd July 2018) - Chirinos, Julio A.; Sardana, Mayank; Oldland, Garrett; Ansari, Bilal; Lee, Jonathan; Hussain, Anila; Mustafa, Anique; Akers, Scott R.; Wei, Wen; Lakatta, Edward G.; Fedorova, Olga V.
Abstract: Aims: The arginine vasopressin (AVP) pathway has been extensively studied in heart failure (HF) with reduced ejection fraction (HFrEF), but less is known about AVP in HF with preserved EF (HFpEF). Furthermore, the association between AVP and atrial natriuretic peptide (ANP, a well‐known inhibitor of AVP secretion) in HF is unknown. Methods and results: We studied subjects with HFpEF ( n = 28) and HFrEF ( n = 25) and without HF ( n = 71). Left ventricular (LV) mass and left atrial (LA) volumes were measured with cardiac magnetic resonance imaging. Arginine vasopressin and ANP were measured with enzyme‐linked immunosorbent assay. Arginine vasopressin levels were significantly greater in HFpEF [0.96 pg/mL; 95% confidence interval (CI) = 0.83–1.1 pg/mL] compared with subjects without HF (0.69 pg/mL; 95% CI = 0.6–0.77 pg/mL; P = 0.0002). Heart failure with preserved ejection fraction (but not HFrEF) was a significant predictor of higher AVP after adjustment for potential confounders. Arginine vasopressin levels were independently associated with a greater LA volume and also paradoxically, with lower ANP levels. Key independent correlates of higher AVP were the presence of HFpEF (standardized β = 0.32; 95% CI = 0.09–0.56; P = 0.0073) and the ANP/LA volume ratio (standardized β = −0.23; 95% CI = −0.42 to −0.04; P = 0.0196). Arginine vasopressin levels were independently associated with LV mass ( β = 0.26; 95% CI = 0.09–0.43; P = 0.003) and with an increased risk of death or HF admissions during follow‐up (hazard ratio = 1.61; 95% CI = 1.13–2.29; P = 0.008). Conclusions: Arginine vasopressin is increased in HFpEF and is associated with LV hypertrophy and poor outcomes. Higher AVP is associated with the combination of LA enlargement and paradoxically low ANP levels. These findings may indicate that a relative deficiency of ANP (an inhibitor of AVP secretion) in the setting of chronically increased LA pressure may contribute to AVP excess.